Performance Evaluation of the Pressing Process to Improve Electrical Energy Efficiency at PT ISM Bogasari Flour Mills Surabaya - Anggara Adji Prananta; Handy Febri Satoto (Telkom University, 2026)
This study aims to evaluate the performance of the pressing process as an effort to improve electrical energy efficiency in the Pelletizing Division of PT ISM Bogasari Flour Mills Surabaya. The research problem is based on the unachieved Key Performance Indicator (KPI) target for the electrical energy consumption ratio of 17.5 kWh/ton, where the actual consumption in 2024 reached 18.705 kWh/ton. The study employs the Objective Matrix (OMAX) method to measure productivity levels based on several performance indicators covering labor, machinery, raw materials, and electrical energy. Research data were obtained from operational production data for the period of July to December 2024. The analysis results indicate that the pressing process accounts for the largest share of energy consumption at 81.23% of total electrical energy waste in the pelletizing process. The implementation of a corrective action in the form of a reprocess raw material pathway relayout was proven effective in improving press machine work effectiveness and reducing electrical energy consumption. The average OMAX productivity increased from 5.10 to 5.34, while the average electrical energy consumption decreased from 18.80 kWh/ton to 16.12 kWh/ton. Furthermore, the company's electrical energy consumption KPI target was successfully achieved following the implementation of the improvement.